Cinacalcet effect on severe hyperparathyroidism - Al Saran Khalid; Sabry Alaa; Yehia Ahmed; Molhem Azeb (Saudi Journal of Kidney Diseases and Transplantation, 2010)
To determine the efficacy and safety of cinacalcet, a calcimimetic drug that suppress parathyroid hormone (PTH) production, we studied its effect on 20 patients (13 males) on maintenance hemodialysis (HD), 80% of them have persistent high PTH levels (i.e. more than 80 pmol/L), the remaining patients had PTH levels more than 60 pmol/L. Five of 20 (25%) patients dropped out from the study (2 because of severe GIT upset, one showed severe myalgia and arthralgia, one patient due to non compliance and one died at home due to cardiac arrest). The remaining 15 patients (10 males) had a mean age of 40 ± 12.86 years and dialysis duration of 29.13 ± 18.27 months. The follow-up period on cinacalcet was 4 months with a single daily oral dose started with 30 mg/day and increased gradually according to the PTH levels. Nine (60%) pa-tients were on concomitant active vitamin D during the study period with a mean dose of 7.33 ± 3.39 μg/week. There was a significant decrease in the serum PTH levels at the end the study compared to that at the start (46.4 ± 4.7 pmol/L versus 93.3 ± 25.6 pmol/L, respectively, P< 0.000), and the target PTH level (< 31.6 pmol/L) was achieved in 54% of patients. No significant changes in serum Ca and phosphorous levels were observed. We conclude that cinacalcet is an effective therapy to suppress the serum PTH levels and allows favorable management of the serum calcium and phosphorus levels in HD patients. The drug was well tolerated; however, GIT discomfort is a significant side effect that may necessitate drug withdrawal in some patients.